Diagnostic workup of childhood interstitial lung disease. (22nd February 2023) - Nathan, Nadia; Griese, Matthias; Michel, Katarzyna; Carlens, Julia; Gilbert, Carlee; Emiralioglu, Nagehan; Torrent-Vernetta, Alba; Marczak, Honorata; Willemse, Brigitte; Delestrain, Céline; Epaud, Ralph
Childhood interstitial lung diseases (chILDs) are rare and heterogeneous diseases with significant morbidity and mortality. An accurate and quick aetiological diagnosis may contribute to better management and personalised treatment. On behalf of the European Respiratory Society Clinical Research Collaboration for chILD (ERS CRC chILD-EU), this review summarises the roles of the general paediatrician, paediatric pulmonologists and expert centres in the complex diagnostic workup. Each patient's aetiological chILD diagnosis must be reached without prolonged delays in a stepwise approach from medical history, signs, symptoms, clinical tests and imaging, to advanced genetic analysis and specialised procedures including bronchoalveolar lavage and biopsy, if necessary. Finally, as medical progress is fast, the need to revisit a diagnosis of "undefined chILD" is stressed. Childhood interstitial lung diseases are rare and severe diseases. A stepwise approach to an aetiological diagnosis includes specific investigations performed in expert centres. The term "undefined chILD" must be regularly reassessed. https://bit.ly/3YIWKvn